Chhattisgarh Agriculture & Tribal Struggles: A Critical Study - Sinha, Sujita (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 4 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2025)
This article delves into the intricate relationship between the evolving agricultural landscape of Chhattisgarh and the socio-economic challenges faced by its tribal communities. It examines the historical context of tribal dependence on natural resources, particularly water, forests, and land, and how modernization and developmental projects have disrupted traditional agricultural practices. Through a critical analysis of government policies, local conflicts, and the impact of climate change, the study highlights the increasing vulnerabilities of tribal populations. It further explores the role of tribal women in agriculture, the challenges in education and healthcare, and the representation of tribal issues in media and cinema. The article emphasizes the need for sustainable agricultural practices, the preservation of tribal languages and cultures, and the empowerment of tribal communities through political representation and legal rights. It argues for a holistic approach that integrates traditional knowledge with modern advancements to ensure the well-being and resilience of Chhattisgarh’s tribal societies.